Myricetin, the Main Flavonoid in Syzygium cumini Leaf, Is a Novel Inhibitor of Platelet Thiol Isomerases PDI and ERp5 - Gaspar, Renato Simões; da Silva, Samira Abdalla; Stapleton, Jennifer; Fontelles, João Lucas de Lima; Sousa, Hiran Reis; Chagas, Vinicyus Teles; Alsufyani, Shuruq; Trostchansky, Andrés; Gibbins, Jonathan M.; Paes, Antonio Marcus de Andrade (Frontiers in Pharmacology, 2020)
Background: Flavonoids have been characterized as a prominent class of compounds to treat thrombotic diseases through the inhibition of thiol isomerases. Syzygium cumini is a flavonoid-rich medicinal plant that contains myricetin and gallic acid. Little is known about the potential anti-platelet properties of S. cumini and its constituent flavonoids. Objective To evaluate the anti-platelet effects and mechanism of action of a polyphenol-rich extract (PESc) from S. cumini leaf and its most prevalent polyphenols, myricetin and gallic acid. Methods PESc, myricetin and gallic acid were incubated with platelet-rich plasma and washed platelets to assess platelet aggregation and activation. In vitro platelet adhesion and thrombus formation as well as in vivo bleeding time were performed. Finally, myricetin was incubated with recombinant thiol isomerases to assess its potential to bind and inhibit these, whilst molecular docking studies predicted possible binding sites. Results: PESc decreased platelet activation and aggregation induced by different agonists. Myricetin exerted potent anti-platelet effects, whereas gallic acid did not. Myricetin reduced the ability of platelets to spread on collagen, form thrombi in vitro without affecting haemostasis in vivo. Fluorescence quenching studies suggested myricetin binds to different thiol isomerases with similar affinity, despite inhibiting only protein disulphide isomerase (PDI) and ERp5 reductase activities (IC50~3.5 μM). Finally, molecular docking studies suggested myricetin formed non-covalent bonds with PDI and ERp5. Conclusions: PESc and its most abundant flavonoid myricetin strongly inhibit platelet function. Additionally, myricetin is a novel inhibitor of ERp5 and PDI, unveiling a new therapeutic perspective for the treatment of thrombotic disorders.